Unveiling Neuropsychological Pathways for Targeted Interventions in Specific Reading Disorders - Nazeer, Naseeha; V., Dr. Muhammed K.; V., Aswathy D.; S., Sheeja; Jacob, Keerthi (South Eastern European Journal of Public Health, 2025)
Reading disorders give rise to significant challenges to academic achievement and daily communication, affecting millions worldwide. These disorders are upheld by specific neuropsychological deficits that disrupt the intricate processes involved in reading accuracy, fluency, and comprehension. This paper explores the neurological correlates of Specific Reading Disorders, offering a detailed analysis of the brain regions implicated in these deficits. By linking these insights to evidence-based intervention strategies, we propose targeted approaches to manage each aspect of reading difficulties. This neuropsychological perspective not only enhances our understanding of the brain's role in reading but also bridges the gap between neuroscience and education, providing a foundation for developing more effective, individualized interventions. The study emphasizes the importance of integrating scientific knowledge of brain function into educational practices to improve outcomes for individuals with Reading Disorders.